2015
DOI: 10.1007/s00018-015-1984-1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of nucleolar and ribosomal proteins in cancer, development, and aging

Abstract: Changes in nucleolar morphology and function are tightly associated with cellular activity, such as growth, proliferation, and cell cycle progression. Historically, these relationships have been extensively examined in cancer cells, which frequently exhibit large nucleoli and increased ribosome biogenesis. Recent findings indicate that alteration of nucleolar activity is a key regulator of development and aging. In this review, we have provided evidences that the nucleolus is not just a housekeeping factor but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 75 publications
1
45
0
1
Order By: Relevance
“…24 Recently, several p53-independent pathways that cause cell cycle arrest or apotptosis in response to alterations of ribosome biogenesis have been described. 25,26 Several findings have shown evidence that a variety of DNA damage agents including 5-FU and L-OHP impair ribosomal biogenesis. 16,27 We have recently demonstrated that human rpL3 acts as stress sensing molecule essential in the cell response to ribosomal stress caused by 5-FU and L-OHP in cancer cells lacking active p53.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, several p53-independent pathways that cause cell cycle arrest or apotptosis in response to alterations of ribosome biogenesis have been described. 25,26 Several findings have shown evidence that a variety of DNA damage agents including 5-FU and L-OHP impair ribosomal biogenesis. 16,27 We have recently demonstrated that human rpL3 acts as stress sensing molecule essential in the cell response to ribosomal stress caused by 5-FU and L-OHP in cancer cells lacking active p53.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, any dysregulation of the steps can cause an anomalous pattern of protein synthesis, especially a specific programme of proteins associated with cell growth control, thus leading to an increase of susceptibility to tumorigenesis11. In particular, the ribosome assembly involves the association of rRNAs and ribosomal proteins, and ectopic production or activation of ribosomal proteins have been actually observed in several cancer types3031, such as RPS6 in NSCLC and non-Hodgkin lymphoma3233; RPS7, RPS15A and RPS20 in colorectal cancer343536; RPL5 and RPL10 in T-cell acute lymphoblastic leukemia37; and RPS14 in 5q- syndrome38, a subtype of myelodysplastic syndrome (MDS) with a high propensity to acute myeloid leukemia (AML).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Warner and McIntosh (Warner and McIntosh, 2009), the following criteria must be met to define extraribosomal functions of RPs: (i) interaction with some nonribosomal components of the cell; (ii) the interaction has physiological effects on cellular functions; (iii) the effects occur away from ribosomes; (iv) the effects do not influence protein synthesis. This section will mainly focus on extraribosomal functions of RPs related to a few key cellular processes whose abnormal regulation would lead to tumorigenesis, including apoptosis, cell cycle arrest, cell proliferation, neoplastic transformation, and cell migration and invasion (de las Heras-Rubio et al, 2014;Takada and Kurisaki, 2015;Wang et al, 2015a) (Table 1).…”
Section: The Extraribosomal Functions Of Rpsmentioning
confidence: 99%